متطلبات تطبيق نظام التكاليف على أساس الأنشطة "ABC" في المؤسسات الاقتصادية الجزائرية: دراسة ميدانية لمجموعة من مؤسسات قطاع الطحن بولاية بسكرة - معاليم، سعاد; حجازي، إسماعيل (جامعة 8 ماي 1945 قالمة, 2018)
This study aimed at the recognition throughout the availability of the factors of the application of the Activity Based costing (ABC) system in industry companies Algerian. For achieving the objectives of the practical aspect of The study, a questionnaire has been designed based on previous studies and the theoretical framework; the questionnaire was distributed to the study community which composed of all companies of Mills sector in BISKRA city. The study results have showed that the main factors for the application of the system ABC are not available at this companies: there is not knowledge and recognition about the ABC system for the superior administration also for the employees in accounting and they don’t know the benefits that can be in the case of an application. Besides this, the leaders that encouraging change and innovation is weak presence factor in this companies. However, there are just two factors that might support the application of Activity-Based costing system in these companies: the organizational culture based on the cooperation values and the open communication, the availability of accounting systems and modern technology.
لقد هدفت هذه الدراسة إلى التعرف على العوامل التي تحكم عملية تطبيق نظام التكاليف على أساس الانشطة ABC في المؤسسات الاقتصادية الوطنية. وقد استهدفت الدراسة عينة عشوائية بسيطة شملت مجموعة من مؤسسات قطاع الطحن بولاية بسكرة حيث تم جمع البيانات الأولية باستخدام الاستمارة التي وزعت على إطارات المؤسسات إلى جانب المقابلات لدعم تحليل وتفسير النتائج. وبعد تحليل النتائج توصلنا في هذه الدراسة إلى أن هناك عاملين فقط يمكنهما أن يساهما في دعم عملية تطبيق نظام ABC وهما: الثقافة التنظيمية القائمة على قيم التعاون والاتصالات المفتوحة والنظم المعلوماتية المحاسبية والتكنولوجية الحديثة وقد بينت النتائج أيضا أنه ليس هناك معرفة أو إدراك لدى الإدارة العليا أو موظفي المحاسبة بنظام ABC ولا بالمزايا التي يمكن أن يوفرها في حالة تطبيقه. كما أن الإدارة العليا لا ترغب في التحول إلى نظام كلفوي حديث لعدم قدرتها تحمل تكاليف نظام كلفوي مكلف. إلى جانب هذا فإن القيادات المشجعة للتغيير والابتكارات عامل ضعيف التواجد في هذه المؤسسات. كما أن الإدارة العليا لا تولي لعملية تكوين المحاسبين لزيادة خبراتهم أهمية كبيرة.
الجزء الثاني. ماي 2018
Keywords: نظم المعلومات المحاسبية -- إدارة التكاليف -- المؤسسات الاقتصادية -- الجزائر